Meningkatkan Hasil Belajar Menyundul dalam Permainan Sepakbola Melalui Model Pembelajaran Kooperatif Tipe Team Games Tournament (TTG) Pada Siswa Kelas X SMA Negeri 7 Ambon - Rumfot, Yusri; Rumahlewang, Emma; Matitaputty, Johanna; Hattu, Mesak (Academy of Education Journal, 2024)
Heading the ball is one of the learning materials for the game of football. Students are required to have competence through understanding and the ability to practice basic head-to-head techniques. The purpose of this study is to determine the improvement of football heading learning outcomes through the TGT learning model in grade X students of SMA Negeri 7 Ambon. This type of research is classroom action research. The implementation of the action takes place in two cycles. The subjects of the study were 26 students in class X. Learning outcomes are determined based on the rubric of assessment of attitudes, knowledge and skills. The results of the study showed that the learning results of heading the ball in cycle I, there were 16 students who had completed or 68.56% with a total score of 1391.25. Meanwhile, 10 students did not complete or 25.80% with a total score of 662.46. In the second cycle, 26 students have met the KKM or (91.01%) with a total score of 2295.72. The results of this study can be concluded that the TGT learning model can improve the learning outcomes of basic dribbling techniques in football games in grade X students of SMA Negeri 7 Ambon.